2017
DOI: 10.1177/0886260517702491
|View full text |Cite
|
Sign up to set email alerts
|

Intimate Partner Violence Among Female OEF/OIF/OND Veterans Who Were Evaluated for Traumatic Brain Injury in the Veterans Health Administration: A Preliminary Investigation

Abstract: Many female veterans have deployed to Operation Enduring Freedom (OEF), Operation Iraqi Freedom (OIF), and Operation New Dawn (OND), and some experience traumatic brain injury (TBI). Although TBI is increasingly recognized as an important health issue for female OEF/OIF/OND veterans, there is little attention to stressful experiences that may exacerbate health problems or hinder recovery among veterans who may have experienced TBI. Lifetime intimate partner violence (IPV) is common among general samples of fem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 50 publications
2
8
2
Order By: Relevance
“…This result indicated that IPV is an enduring problem and it is not relieved by changes in external circumstances. This result is congruent with Iverson et al (2017), who reported that IPV is a lifelong problem. Moreover, the WHO states that women during a period of quarantine face difficulties in seeking help and support from personal and formal helping resources.…”
Section: Discussionsupporting
confidence: 90%
“…This result indicated that IPV is an enduring problem and it is not relieved by changes in external circumstances. This result is congruent with Iverson et al (2017), who reported that IPV is a lifelong problem. Moreover, the WHO states that women during a period of quarantine face difficulties in seeking help and support from personal and formal helping resources.…”
Section: Discussionsupporting
confidence: 90%
“…Female military veterans are 1.6 times more likely to experience domestic violence throughout their lifetime as compared with women who are not veterans [ 21 , 22 ]. These women are more likely to be abused during their time in the military as well as after.…”
Section: Prevalence and Demographics Of Tbi Related To Domestic Violencementioning
confidence: 99%
“…Due to their time in the military and their increased risk of abuse, they are also more likely to have mental health conditions including a diagnosis of substance abuse. It is important that providers spend time with these patients when diagnosing, because their mental health symptoms could easily be attributed to not only their time in the military [ 22 ]. This can be detrimental to the patient, as many of them need treatment that is specific to survivors of domestic violence.…”
Section: Prevalence and Demographics Of Tbi Related To Domestic Violencementioning
confidence: 99%
“…A large subset of Veterans that sustained a TBI in theater also experience intimate partner violence (IPV). In a study by Iverson et al, 105 a subset of women from a reintegration study reported experiencing lifetime IPV. Those that experienced IPV reported greater neurobehavioral symptoms and were more likely to be clinically diagnosed with back pain or substance abuse.…”
Section: Domestic Violencementioning
confidence: 99%